Effectiveness of Occupational Health and Safety (OHS) Technical Guidance on Improving the Knowledge of OHS Personnel - Arif Sumarianto; Iwan Muhamad Ramdan; Ida Ayu Indira Dwika Lestari (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : One of the requirements for Occupational Health and Safety (OHS) in the workplace is the availability of competent personnel who possess authority in managing workplace environmental safety. Technical guidance is an important strategy to strengthen personnel competency, yet its effectiveness must be evaluated systematically. Objective : To analyze the effectiveness of OHS technical guidance using the Kirkpatrick Model level 2 evaluation. Research Methods / Implementation Methods : This descriptive-analytical study employed a one- group pre-test post-test design. Pre-test assessments were conducted before participants received the training materials, followed by post-test assessments afterward. A total sampling technique was used, involving 25 participants of the OHS Technical Guidance for the Workplace Environment organized by Balai K3 Samarinda on October 21–24, 2025. Results : Statistical analysis showed a significant difference between pre-test and post-test scores, indicating an improvement in participants’ knowledge following the training sessions. Conclusion / Lesson Learned : The OHS Technical Guidance for the Workplace Environment was effective in improving participant knowledge and was successfully implemented with a well- executed training process.